STRATEGI HUMAS SEKRETARIAT DAERAH KABUPATEN ROKAN HULU DALAM MEMBERIKAN INFORMASI KEPADA MASYARAKAT - Rosmala, Rosmala (Ensiklopedia of Journal, 2018)
This study aims to determine the extent of the strategy of Public Relations Regional Secretariat Rokan Hulu District in providing information to the public. Informants in this study are officials authorized in the organizational structure of Public Relations Division Regional Secretariat Rokan Hulu. The results of this study indicate that the implementation of public relations tasks Rokan Hulu District as a drafter and implementer of public relations functions as a liaison with the relevant parties, especially in the field of information, the creation of a smooth relationship, can build mutual trust and also mutual respect and achievement of information delivery Accurate. Proposed suggestion is public relations officer must be able to maximize performance in relationship with media so that publicity will be achieved as expected.